Criminal law and procedure - Scheb, John M. (Thomson Wadsworth, 2008)
Important recent developments, intriguing cases, broad coverage of law and procedures...this practical, up-to-date book gives you everything you need to understand the substantive and procedural aspects of criminal law. Ideal for criminal justice, pre-law, and paralegal students, CRIMINAL LAW AND PROCEDURE includes useful student aids to help you master the material and succeed in your course. Praised for its currency, CRIMINAL LAW AND PROCEDURE includes timely topics such as the post-9-11 environment; the recent surge in white-collar crime, cybercrime, and identity theft; military courts; new sentencing guidelines; and more